Lithium slag filled paper and preparation method thereof
By pretreating the lithium slag waste with weak acid and mixing it with plant fiber slurry, lithium slag and filler paper is prepared, which solves the problems of poor strength and low retention of existing papermaking fillers, and efficient utilization of lithium slag waste is achieved, reducing production costs and environmental pollution.
Patent Information
- Application Number
- CN202310788692.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-30
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2043-06-30
AI Technical Summary
The existing paper-making filler has poor paper strength and low filler retention rate. The addition of filler will reduce the strength performance of paper sheets. The treatment method of lithium slag is limited, resulting in waste of resources and environmental pollution.
By pretreating the lithium slag waste with weak acid, lithium slag filler is prepared, and mixed with the plant fiber slurry, adding a retention filter aid to prepare paper slurry, and the lithium slag is added to obtain the paper slurry by web forming, pressing and drying.
The mechanical strength and filler retention rate of lithium slag added paper are improved, the amount and production cost of plant fibers are reduced, the types and application scope of added paper are expanded, and the recycling of lithium slag waste is realized, reducing environmental pollution.
Smart Images

Figure CN116752381B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of papermaking fillers, and in particular to lithium slag filled paper and a preparation method thereof. Background Art
[0002] At present, the papermaking industry is facing increasing competitive pressure, with rising raw material costs, higher product quality requirements, and declining sales prices. In the papermaking industry, mineral fillers, as the second largest raw material, play a vital role in improving paper performance, reducing production costs, and reducing carbon emissions in nature. Common fillers in the papermaking industry are mainly light calcium carbonate (PCC), heavy calcium carbonate (GCC), kaolin and talcum powder. Compared with plant fibers, mineral fillers have the characteristics of small particle size, high whiteness, high refractive index, and low water absorption. Adding them to paper can effectively improve the quality of paper (such as opacity, smoothness, printing adaptability, softness, uniformity and dimensional stability, etc.), and the price of mineral fillers is generally lower than that of plant fibers. The price of commonly used calcium carbonate fillers on the market is usually 10%-20% of chemical pulp, while the filler content in daily paper is now 20%-40%. Therefore, replacing higher-cost plant fibers with lower-cost mineral fillers and increasing the filler content in paper is conducive to reducing the raw material cost in paper production. In addition, using mineral fillers instead of plant fibers can also improve pulp filtration, reduce paper moisture, and thus reduce paper drying costs. Using papermaking fillers instead of plant fibers can also reduce plant resource consumption and steam energy consumption, which means less carbon emissions, in line with the requirements of my country's "dual carbon" strategy.
[0003] Since papermaking fillers are generally inorganic mineral powders, there is no chemical bonding ability between the filler particles themselves and the fibers, so adding fillers usually reduces the strength of the finished paper. In the prior art, in order to improve the strength of filled paper, various additives are used to combine filler particles with fibers through bridging adsorption. In addition, the strength of the paper can be improved by increasing the beating degree of the fibers to increase the content of fine fibers, making the fibers more closely interwoven, but this will also reduce the water filtration performance of papermaking to a certain extent. Secondly, it is to use filler modification technology, such as improving filler performance through starch coating, composite modification by co-grinding nanocellulose and calcium carbonate, and so on. Compared with the filler before modification, these methods have increased the strength performance of the paper to a certain extent, but the filler modification technology is usually technically difficult and costly.
[0004] Lithium slag is a byproduct of lithium carbonate extraction from lithium ore. In recent years, with the huge production of lithium salts in my country, the amount of waste lithium slag has also increased in the same proportion. The current treatment method of lithium slag is mainly as a cement admixture. However, in recent years, the doping content of lithium slag in the concrete industry has been decreasing, generally not exceeding 5%. In actual production, it is usually only 1%-3%. Moreover, with the gradual saturation of domestic infrastructure, the demand for cement in the overall environment is also decreasing, resulting in the output of lithium slag far exceeding the demand. Therefore, a large part of the remaining lithium slag can only be treated by landfill or open-air stacking, which not only occupies land resources, but also brings great burden to the natural environment with the evolution of a series of natural climates such as wind and rain.
[0005] Lithium slag is a block structure, and its chemical composition is mainly silicon oxide, aluminum oxide, calcium oxide and a small amount of sulfur trioxide, which is similar to the composition of talcum powder, kaolin and other traditional paper fillers. Lithium slag has a small particle size and a large specific surface area. To a certain extent, it is feasible to use it as a paper filler. However, there are few reports on lithium slag as a paper filler. Therefore, how to use lithium slag as a paper filler to prepare a filler paper that guarantees the strength performance and retention rate of paper and reduces the amount of plant fiber in paper and the production cost has become a technical problem that needs to be overcome. Summary of the invention
[0006] The invention provides lithium slag filled paper which can improve strength performance and increase retention rate, reduce the amount of plant fiber in paper and production cost, and a preparation method thereof, so as to solve the problems of poor paper strength, low filler retention rate and reduced paper sheet strength performance due to the addition of fillers in existing papermaking fillers.
[0007] To achieve the above object, the present invention provides a method for preparing lithium slag filled paper, comprising:
[0008] 1) providing a lithium slag filler, wherein the lithium slag filler is prepared by pre-treating lithium slag waste; and providing a lithium slag filler liquid, wherein the lithium slag filler liquid comprises the lithium slag filler and deionized water;
[0009] 2) providing a mixed slurry, wherein the mixed slurry is prepared by debonding and refining a plant fiber pulp board;
[0010] 3) mixing the lithium slag filler liquid with the mixed slurry, and adding a retention and filtration aid to obtain a paper slurry;
[0011] 4) After the paper pulp is formed on the screen, it is pressed and dried to obtain lithium slag filled paper; the pretreatment of the above lithium slag waste includes acid treatment, and the acid used for the acid treatment is a weak acid, which is at least one of phosphoric acid, oxalic acid, and acetic acid.
[0012] Through the above technical solution, the lithium slag waste is pretreated and used as papermaking filler, which can improve the mechanical strength of the filled paper, and the pretreated lithium slag filler can improve the whiteness of the lithium slag filled paper to a certain extent. Compared with the existing light calcium carbonate filled paper, the lithium slag filled paper effectively improves the tensile index, tear index and other strength properties of the filled paper, and also reduces the production cost, greatly expanding the types and application range of the filled paper made of the existing filler.
[0013] It is further configured that the pretreatment steps of the lithium slag waste are as follows: using a weak acid solution to stir and soak the lithium slag waste, then washing the lithium slag waste with deionized water until the obtained filtrate is neutral, filtering, taking the filtrate and drying it to obtain a lithium slag filler.
[0014] Further preferably, the lithium slag waste is in a block structure with an average particle size of 13.93 μm.
[0015] When lithium slag waste is directly used as papermaking filler, the whiteness of the obtained lithium slag filled paper is low and the color of the filled paper is yellowish. After weak acid pretreatment, some metals and their oxides in the lithium slag waste can be dissolved and washed away, which can effectively improve and enhance the whiteness of the filled paper. In addition, after the lithium slag waste is pretreated with weak acid, the average particle size is reduced and the specific surface area is increased, so that the surface wettability of the lithium slag filler is improved, and more sites for combining with fibers are formed, so that the lithium slag filler can collide and combine with the fibers more conveniently, and some of them can also be embedded in the gaps between the fibers, which improves the degree of combination between the lithium slag filler and the fibers, and is conducive to increasing the retention rate of the lithium slag filler.
[0016] It is further configured that, in the weak acid solution, the mass concentration of the weak acid is 0.1%-12%; the stirring rate of the stirring and immersion is 700rpm-1000rpm, and the time is 0.5h-2h; the drying temperature is 100℃-115℃, and the time is 4h-7h.
[0017] It is further configured that the preparation steps of the lithium slag filler liquid are as follows: the lithium slag filler and deionized water are mixed to prepare a suspension, and then the suspension is magnetically stirred to obtain the lithium slag filler liquid.
[0018] It is further configured that the mass concentration of the lithium slag filler in the suspension is 8%-12%; the rotation speed of the magnetic stirring is 900rpm-1200rpm, and the stirring time is 20min-40min.
[0019] It is further configured that the plant fiber pulp board is a broadleaf pulp board and a coniferous wood pulp board; the mass ratio of the broadleaf pulp board to the coniferous wood pulp board is (2.5-3.5):1; and the beating degree of the mixed pulp is 35°SR-45°SR.
[0020] After the plant fibers in the mixed pulp are deflated and refined, under the action of mechanical shear force, the fibers in the mixed pulp have good dispersion, contain a large number of exposed hydroxyl groups on the surface, and can form hydrogen bonds between the fibers, which is also conducive to a closer combination of the fibers and the lithium slag filler, so that the fibers can load the lithium slag filler and improve the retention rate of the lithium slag filler, while ensuring the strength performance of the filled paper and improving the problem of reduced strength performance of the filled paper due to the addition of fillers.
[0021] It is further configured that the amount of lithium slag filler added to the paper slurry is 8%-25% of the mass of the mixed slurry.
[0022] It is further configured that the retention and drainage aid is at least one of cationic starch, cationic polyacrylamide, cationic polyethyleneimine, cationic chitosan, and cationic guar gum, and the mass proportion of the retention and drainage aid in the paper stock slurry is 0.01%-2%.
[0023] Further preferably, the retention and drainage aid comprises cationic polyacrylamide, which is configured into an aqueous solution with a mass concentration of 0.05% before use. In a specific example, after adding the retention and drainage aid, uniform stirring is provided for 5s-10s. The retention and drainage aid can increase the bonding ability between fillers and fillers, and between fillers and fibers, and plays a bridging role between lithium slag fillers and fibers, which is beneficial to improving the retention rate of fillers in the filled paper and the strength of the paper, and also improves the utilization rate of the lithium slag fillers.
[0024] It is further set that, when the web is formed, the web mass concentration is 0.02%-0.03%, the web speed is 150m / min-300m / min, the pulp-web speed ratio is 0.96-1.01; the pressing pressure is 0.3MPa-0.5MPa, and the time is 3min-5min; the drying temperature is 100℃-115℃, and the time is 7min-12min.
[0025] On the other hand, the present invention also provides a lithium slag filled paper, comprising: prepared by the above-mentioned preparation method of lithium slag filled paper; the basis weight of the lithium slag filled paper is 65g / m 2 -80g / m 2 The lithium slag filled paper is uniform and dense, has high paper strength and filler retention rate, high raw material utilization rate, low production cost, and greatly expands the types and application range of filled paper made from existing fillers.
[0026] In addition, the present invention also provides an application of lithium slag waste in the field of papermaking, wherein the lithium slag waste is used as a papermaking filler for preparing filled paper; and the lithium slag waste is pretreated with a weak acid, wherein the weak acid is at least one of phosphoric acid, oxalic acid, and acetic acid. The lithium slag waste can be used as a papermaking filler after acid treatment, which provides a new recycling method for lithium slag waste, and at the same time provides filled paper that is different from existing fillers, thereby expanding the types and application scope of filled paper.
[0027] The lithium slag filled paper and the preparation method thereof provided by the present invention achieve the following beneficial effects by recycling lithium slag waste as papermaking filler:
[0028] 1) In the present invention, lithium slag is used as a papermaking filler for papermaking. Compared with traditional papermaking fillers, the tensile index, tear index and other strength performance indicators of the obtained lithium slag filled paper are significantly improved. The preparation method of the present invention can prepare lithium slag filled paper with different strength properties and different tightness by changing the filler addition amount, so that the quality of the lithium slag filled paper is controllable, and the preparation method is simple to operate, has low equipment requirements, is environmentally friendly, is easy to industrialize, can reduce the consumption of plant fiber resources, has broad application prospects, and is of great significance to reducing costs and sustainable development in the papermaking industry.
[0029] 2) The present invention uses weak acid to pretreat lithium slag waste, which can improve the whiteness and strength performance of filled paper to a certain extent, and can also improve the retention rate and tensile strength of the filler in the filled paper. It also improves the problems of low filler retention rate and lack of bonding strength between fillers and between fillers and fibers in the existing filled paper. Compared with lithium slag waste that has not been treated with acid, after lithium slag filler is used for paper filling, the tear strength, whiteness and retention rate of the paper are significantly improved, the tensile strength is slightly reduced, and the load of the papermaking white water system and the wastewater treatment load are also reduced.
[0030] 3) The lithium slag filled paper of the present invention is uniform and dense, has high paper strength and filler retention rate, also has high raw material utilization rate, low production cost, greatly expands the types and application range of filled paper made from existing fillers, also realizes the recycling and reuse of lithium slag waste, effectively improves the pollution problem of lithium slag waste, and has environmental and ecological benefits. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the following briefly introduces the drawings required for use in the embodiments or the description of the prior art. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1The microscopic morphology of different papermaking fillers, a-Comparative Example 1, b-Example 4, c-Comparative Example 5;
[0033] Figure 2 Microscopic morphology images of different filled papers, a-Comparative Example 1, b-Example 4. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention is clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work also fall within the scope of protection of the present invention.
[0035] The following examples use conventional instruments and equipment in the art. Unless otherwise specified, the test materials and reagents used in the following examples can be obtained from commercial sources, and their specifications are conventional specifications in the art. If no specific techniques or conditions are specified in the following examples, they can be carried out according to the techniques or conditions described in the literature in the art or according to the product instructions.
[0036] It should be noted that, in the present invention and the following embodiments, concentrations, ratios, etc. not otherwise specified are all weight concentrations, weight ratios, etc., "%" means weight percentage, and "parts" means parts by weight, which are common writing habits used by those skilled in the art and are therefore not described in detail in the present invention.
[0037] In a specific embodiment, a method for preparing lithium slag filled paper of the present invention comprises the following steps:
[0038] 1) Using a weak acid solution with a mass concentration of 0.1%-12% to stir and soak the lithium slag waste, then washing the lithium slag waste with deionized water until the filtrate is neutral, filtering, taking the filter residue and drying it to obtain a lithium slag filler. The lithium slag waste is a block structure with an average particle size of 13.93 μm. The weak acid is at least one of phosphoric acid, oxalic acid, and acetic acid. The stirring rate of the stirring and soaking is 700rpm-1000rpm, and the time is 0.5h-2h; the drying temperature is 100℃-115℃, and the time is 4h-7h.
[0039] 2) Mixing lithium slag filler and deionized water to prepare a suspension with a lithium slag filler mass concentration of 8%-12%, and then subjecting the suspension to magnetic stirring to obtain a lithium slag filler liquid. The magnetic stirring speed is 900rpm-1200rpm, and the stirring time is 20min-40min.
[0040] 3) Mix the hardwood pulp board and the softwood pulp board in a mass ratio of (2.5-3.5):1, deflagrate them with a deflagrator, and then refine them with a PFI refiner to obtain a mixed pulp with a beating degree of 35°SR-45°SR.
[0041] 4) Mixing the lithium slag filler liquid with the mixed slurry, adding a retention and drainage aid, and stirring at a constant speed for 5s-10s to obtain a paper stock slurry; in the above paper stock slurry, the addition amount of the lithium slag filler is 8%-25% of the mass of the mixed slurry. The above retention and drainage aid is at least one of cationic starch, cationic polyacrylamide, cationic polyethyleneimine, cationic chitosan, and cationic guar gum, and the mass proportion of the retention and drainage aid in the paper stock slurry is 0.01%-2%.
[0042] Preferably, the retention and drainage aid is cationic polyacrylamide, which should be prepared into an aqueous solution with a mass concentration of 0.05% before use.
[0043] 5) After the paper pulp is formed on the screen, it is pressed and dried to obtain a basis weight of 65g / m 2 -80g / m 2 When forming the web, the web mass concentration is 0.02%-0.03%, the web speed is 150m / min-300m / min, the pulp-web speed ratio is 0.96-1.01; the pressing pressure is 0.3MPa-0.5MPa, the time is 3min-5min; the drying temperature is 100℃-115℃, and the time is 7min-12min.
[0044] It should be noted that the mixed pulp of the present invention may also include other papermaking pulps, including but not limited to grass pulp, reed pulp, straw pulp, poplar bleached chemical mechanical pulp, etc. Functional additives such as softeners, water absorbents, wet strength agents, etc. may also be added to the paper pulp to meet consumers' demands for softness, water absorption effect, and other functions of the filled paper.
[0045] The present invention is further described in detail below in conjunction with the examples. However, it should be understood that the examples are for illustrative purposes only and are not intended to limit the scope of the present invention.
[0046] Embodiment 1:
[0047] A method for preparing lithium slag filled paper comprises the following steps:
[0048] 1) Using a weak acid solution with a mass concentration of 1% and stirring at a speed of 700 rpm to soak the lithium slag waste for 2 hours, then washing the lithium slag waste with deionized water until the filtrate is neutral, filtering, and drying the filtrate at a temperature of 100° C. for 7 hours to obtain a lithium slag filler. The above-mentioned lithium slag waste is a block structure with an average particle size of 13.93 μm. The above-mentioned weak acid is phosphoric acid.
[0049] 2) The lithium slag filler and deionized water are mixed to prepare a suspension having a lithium slag filler mass concentration of 8%, and then the suspension is magnetically stirred at a rotation speed of 900 rpm for 40 minutes to obtain a lithium slag filler liquid.
[0050] 3) After mixing the hardwood pulp board and the softwood pulp board in a mass ratio of 2.5:1, the mixture was deflaked by a deflaker, and then refined by a PFI refiner to obtain a mixed pulp with a beating degree of 35° SR.
[0051] 4) Mixing the lithium slag filler liquid with the mixed slurry, adding a retention and drainage aid, and stirring at a constant speed for 5 seconds to obtain a paper stock slurry; in the above paper stock slurry, the addition amount of the lithium slag filler is 8% of the mass of the mixed slurry. The above retention and drainage aid is cationic starch, and the mass proportion of the retention and drainage aid in the paper stock slurry is 0.1%.
[0052] 5) After the paper pulp is formed on the net under the conditions of a net mass concentration of 0.02%, a net speed of 150m / min, and a pulp-to-net speed ratio of 0.96, it is pressed for 5 minutes under a pressure of 0.3MPa, and then dried for 12 minutes at a temperature of 100℃ to obtain a paper with a basis weight of 65g / m 2 Lithium slag plus filler paper.
[0053] Embodiment 2:
[0054] A method for preparing lithium slag filled paper comprises the following steps:
[0055] 1) Using a weak acid solution with a mass concentration of 12% at a speed of 1000 rpm to stir and soak the lithium slag waste for 0.5 h, then washing the lithium slag waste with deionized water until the filtrate is neutral, filtering, and drying the filtrate at a temperature of 115° C. for 4 h to obtain a lithium slag filler. The above-mentioned lithium slag waste is a block structure with an average particle size of 13.93 μm. The above-mentioned weak acid is oxalic acid.
[0056] 2) The lithium slag filler and deionized water were mixed to prepare a suspension having a lithium slag filler mass concentration of 12%, and then the suspension was magnetically stirred at a rotation speed of 1200 rpm for 20 minutes to obtain a lithium slag filler liquid.
[0057] 3) After mixing the hardwood pulp board and the softwood pulp board in a mass ratio of 3.5:1, the mixture was deflaked by a deflaker and then refined by a PFI refiner to obtain a mixed pulp with a beating degree of 45° SR.
[0058] 4) Mixing the lithium slag filler liquid with the mixed slurry, adding a retention and drainage aid, and stirring at a constant speed for 10 seconds to obtain a paper stock slurry; in the above paper stock slurry, the addition amount of the lithium slag filler is 25% of the mass of the mixed slurry. The above retention and drainage aid is cationic chitosan, and the mass proportion of the retention and drainage aid in the paper stock slurry is 2%.
[0059] 5) After the paper stock pulp is formed on the net under the conditions of a net mass concentration of 0.03%, a net speed of 300m / min, and a pulp-to-net speed ratio of 1.01, it is pressed for 3min under a pressure of 0.5MPa, and then dried for 7min at a temperature of 115℃ to obtain a paper stock with a basis weight of 80g / m 2 Lithium slag plus filler paper.
[0060] Embodiment 3:
[0061] A method for preparing lithium slag filled paper comprises the following steps:
[0062] 1) Using a weak acid solution with a mass concentration of 8% and stirring at a speed of 900 rpm to soak the lithium slag waste for 1 hour, then washing the lithium slag waste with deionized water until the filtrate is neutral, filtering, and drying the filtrate at a temperature of 110° C. for 5 hours to obtain a lithium slag filler. The above-mentioned lithium slag waste is a block structure with an average particle size of 13.93 μm. The above-mentioned weak acid is acetic acid.
[0063] 2) The lithium slag filler and deionized water were mixed to prepare a suspension having a lithium slag filler mass concentration of 9%, and then the suspension was magnetically stirred at a rotation speed of 1100 rpm for 25 minutes to obtain a lithium slag filler liquid.
[0064] 3) After mixing the hardwood pulp board and the softwood pulp board in a mass ratio of 3.2:1, the mixture was deflaked by a deflaker, and then refined by a PFI refiner to obtain a mixed pulp with a beating degree of 38° SR.
[0065] 4) Mixing the lithium slag filler liquid with the mixed slurry, adding a retention and drainage aid, and stirring at a constant speed for 10 seconds to obtain a paper stock slurry; in the above paper stock slurry, the addition amount of the lithium slag filler is 17.5% of the mass of the mixed slurry. The above retention and drainage aid is cationic guar gum, and the mass proportion of the retention and drainage aid in the paper stock slurry is 0.5%.
[0066] 5) After the paper pulp is formed on the net under the conditions of a net mass concentration of 0.023%, a net speed of 250m / min, and a pulp-to-net speed ratio of 0.99, it is pressed for 3 minutes under a pressure of 0.35MPa, and then dried for 10 minutes at a temperature of 110°C to obtain a paper pulp with a basis weight of 73g / m 2 Lithium slag plus filler paper.
[0067] Embodiment 4:
[0068] A method for preparing lithium slag filled paper comprises the following steps:
[0069] 1) Using oxalic acid solution with a mass concentration of 6% to stir and soak the lithium slag waste for 1 hour at a speed of 800 rpm, then washing the lithium slag waste with deionized water until the filtrate is neutral, filtering, and drying the filtrate at a temperature of 105° C. for 6 hours to obtain a lithium slag filler. The lithium slag waste is a block structure with an average particle size of 13.93 μm.
[0070] 2) The lithium slag filler and deionized water are mixed to prepare a suspension having a lithium slag filler mass concentration of 10%, and then the suspension is magnetically stirred at a rotation speed of 1000 rpm for 30 minutes to obtain a lithium slag filler liquid.
[0071] 3) After mixing the hardwood pulp board and the softwood pulp board in a mass ratio of 3:1, the mixture was deflaked by a deflaker, and then refined by a PFI refiner to obtain a mixed pulp with a beating degree of 42° SR.
[0072] 4) Mixing the lithium slag filler liquid with the mixed slurry, adding a retention and drainage aid, and stirring at a constant speed for 10 seconds to obtain a paper stock slurry; in the above paper stock slurry, the addition amount of the lithium slag filler is 8% of the mass of the mixed slurry. The above retention and drainage aid is cationic polyacrylamide, which should be prepared into an aqueous solution with a mass concentration of 0.05% before use, and the amount of the above cationic polyacrylamide solution is 0.6mL.
[0073] 5) After the paper pulp is formed on the screen at a screen mass concentration of 0.025%, a screen speed of 230m / min, and a pulp-to-screen speed ratio of 0.98, it is pressed for 4min at a pressure of 0.4MPa and then dried at a temperature of 105℃ for 9min to obtain a paper pulp with a basis weight of 70g / m 2 Lithium slag plus filler paper.
[0074] Embodiment 5:
[0075] A method for preparing lithium slag filled paper, the rest of the preparation process and experimental parameters are the same as those in Example 4, the only difference is that in step 1), the weak acid solution used is an oxalic acid solution with a mass concentration of 12%.
[0076] Embodiment 6:
[0077] A method for preparing lithium slag filled paper, wherein the rest of the preparation process and experimental parameters are the same as those in Example 4, except that in step 4), the amount of lithium slag filler added to the paper slurry is 15% of the mass of the mixed slurry.
[0078] Embodiment 7:
[0079] A method for preparing lithium slag filled paper, wherein the rest of the preparation process and experimental parameters are the same as those in Example 5, except that in step 4), the amount of lithium slag filler added to the paper slurry is 15% of the mass of the mixed slurry.
[0080] Embodiment 8:
[0081] A method for preparing lithium slag filled paper, wherein the rest of the preparation process and experimental parameters are the same as those in Example 4, except that in step 4), the amount of lithium slag filler added to the paper slurry is 20% of the mass of the mixed slurry.
[0082] Embodiment 9:
[0083] A method for preparing lithium slag filled paper, wherein the rest of the preparation process and experimental parameters are the same as those in Example 5, except that in step 4), the amount of lithium slag filler added to the paper slurry is 20% of the mass of the mixed slurry.
[0084] Embodiment 10:
[0085] A method for preparing lithium slag filled paper, wherein the rest of the preparation process and experimental parameters are the same as those in Example 4, except that in step 4), the amount of lithium slag filler added to the paper slurry is 25% of the mass of the mixed slurry.
[0086] Embodiment 11:
[0087] A method for preparing lithium slag filled paper, the rest of the preparation process and experimental parameters are the same as those in Example 5, the only difference is that: in step 4), the amount of lithium slag filler added to the paper slurry is 25% of the mass of the mixed slurry.
[0088] Embodiment 12:
[0089] A preparation method of lithium slag filled paper is further optimized on the basis of the aforementioned implementation manner and examples of the present invention, and the optimization measures are as follows: 0.1wt%-0.5wt% of aminotri(methylenephosphonic acid) and 0.3wt%-1.0wt% of tea polyphenols are also added to the paper stock slurry. The two cooperate to form hydrogen bonds with the groups between fibers, and can also form links with the lithium slag filler by using their groups, so that the lithium slag filler can form a more stable entanglement and link with the fibers with the help of the two, so that the filler and the fibers, and the fibers and the fibers inside the paper form a more complex mechanical entanglement, thereby improving the internal compactness of the filled paper and the retention rate of the lithium slag filler, and also improving the strength performance of the filled paper.
[0090] In this embodiment, a method for preparing lithium slag filled paper is provided. The rest of the preparation process and experimental parameters are the same as those in Example 4, except that in step 4), 0.3 wt % of aminotri(methylenephosphonic acid) and 0.6 wt % of tea polyphenols are added to the paper slurry.
[0091] Comparative Example 1:
[0092] A method for preparing lithium slag filled paper, the rest of the preparation process and experimental parameters are the same as those in Example 4, the only difference is that in step 1), the weak acid solution used is an oxalic acid solution with a mass concentration of 0%.
[0093] Comparative Example 2:
[0094] A method for preparing lithium slag filled paper, wherein the rest of the preparation process and experimental parameters are the same as those in comparative example 1, except that in step 4), the amount of lithium slag filler added to the paper slurry is 15% of the mass of the mixed slurry.
[0095] Comparative Example 3:
[0096] A method for preparing lithium slag filled paper, wherein the rest of the preparation process and experimental parameters are the same as those in comparative example 1, except that in step 4), the amount of lithium slag filler added to the paper slurry is 20% of the mass of the mixed slurry.
[0097] Comparative Example 4:
[0098] A method for preparing lithium slag filled paper, wherein the rest of the preparation process and experimental parameters are the same as those in comparative example 1, except that in step 4), the amount of lithium slag filler added to the paper slurry is 25% of the mass of the mixed slurry.
[0099] Comparative Example 5:
[0100] A method for preparing calcium carbonate filled paper comprises the following steps:
[0101] 1) Select precipitated calcium carbonate as a filler for papermaking, add deionized water to prepare a suspension with a mass concentration of 10%, and then stir the suspension with a magnetic force at a speed of 1000 rpm for 30 minutes to obtain a calcium carbonate filler liquid. The precipitated calcium carbonate is a block structure with an average particle size of 4.530 μm.
[0102] 2) After mixing the hardwood pulp board and the softwood pulp board in a mass ratio of 3:1, the mixture was deflaked by a deflaker, and then refined by a PFI refiner to obtain a mixed pulp with a beating degree of 42° SR.
[0103] 3) Mixing the calcium carbonate filler liquid with the mixed slurry, adding a retention and drainage aid, and stirring at a constant speed for 10 seconds to obtain a paper stock slurry; in the above paper stock slurry, the addition amount of precipitated calcium carbonate is 8% of the mass of the mixed slurry. The above retention and drainage aid is cationic polyacrylamide, which should be prepared into an aqueous solution with a mass concentration of 0.05% before use, and the amount of the above cationic polyacrylamide solution is 0.6mL.
[0104] 4) After the paper pulp is formed on the net under the conditions of a net mass concentration of 0.025%, a net speed of 230m / min, and a pulp-to-net speed ratio of 0.98, it is pressed for 4min under a pressure of 0.4MPa and then dried at a temperature of 105℃ for 9min to obtain a paper pulp with a basis weight of 70g / m 2 Calcium carbonate filled paper.
[0105] Comparative Example 6:
[0106] A method for preparing calcium carbonate-filled paper, wherein the rest of the preparation process and experimental parameters are the same as those in comparative example 5, except that in step 3), the amount of precipitated calcium carbonate added to the paper stock slurry is 15% of the mass of the mixed slurry.
[0107] Comparative Example 7:
[0108] A method for preparing calcium carbonate-filled paper, wherein the rest of the preparation process and experimental parameters are the same as those in comparative example 5, except that in step 3), the amount of precipitated calcium carbonate added to the paper stock slurry is 20% of the mass of the mixed slurry.
[0109] Comparative Example 8:
[0110] A method for preparing calcium carbonate-filled paper, wherein the rest of the preparation process and experimental parameters are the same as those in comparative example 5, except that in step 3), the amount of precipitated calcium carbonate added to the paper slurry is 25% of the mass of the mixed slurry.
[0111] Comparative Example 9:
[0112] A method for preparing lithium slag filled paper, the rest of the preparation process and experimental parameters are the same as those in Example 12, the only difference is that in step 4), 0.3wt% of aminotri(methylenephosphonic acid) is also added to the paper slurry.
[0113] Comparative Example 10:
[0114] A method for preparing lithium slag filled paper, wherein the rest of the preparation process and experimental parameters are the same as those in Example 12, except that: in step 4), 0.6 wt % of tea polyphenols is also added to the paper slurry.
[0115] Comparative Example 11:
[0116] A method for preparing lithium slag filled paper, wherein the rest of the preparation process and experimental parameters are the same as those in Example 12, except that in step 4), 1.0 wt % of aminotri(methylenephosphonic acid) and 0.6 wt % of tea polyphenols are also added to the paper slurry.
[0117] Comparative Example 12:
[0118] A method for preparing lithium slag filled paper, wherein the rest of the preparation process and experimental parameters are the same as those in Example 12, except that in step 4), 0.3 wt % of aminotri(methylenephosphonic acid) and 1.5 wt % of tea polyphenols are also added to the paper slurry.
[0119] Test Example 1:
[0120] Characterization and determination of different papermaking fillers
[0121] Determination samples: The lithium slag filler, lithium slag waste and precipitated calcium carbonate in Example 4, Comparative Example 1 and Comparative Example 5 were taken as test samples for determination. Three parallels were set for each test sample, and the average value was taken. The results are shown in Tables 1 and Figure 1 shown.
[0122] Determination method: (1) Microscopic morphology: stick conductive glue on the sample table, evenly apply the sample on the conductive glue and press it firmly. After gold spraying, place the sample table in a scanning electron microscope, observe and record the filler morphology in a vacuum environment with a voltage of 20kV. (2) Particle size detection: mix the sample with deionized water to prepare a 10wt% filler dispersion, slowly add it to the particle size analyzer, and test the particle size distribution of the sample by laser light scattering scanning. (3) Specific surface area detection: place the dry sample in the specific surface area analyzer, and use the gas adsorption principle to perform isothermal adsorption and desorption analysis to detect the specific surface area of the sample. (4) Whiteness detection: spread the sample evenly in the sample press to obtain a filler sample with a dense and flat surface, and place it under an intelligent digital whiteness meter for detection. (5) Sedimentation volume determination: prepare a measuring cylinder with a range of 100mL and a minimum scale of 1mL; add 10.0g of sample into the measuring cylinder and soak it in water for 2h; add water to the 100mL mark after soaking, stir and shake well, let it stand at room temperature for 24h, and record the volume of the sample sediment in the measuring cylinder. The ratio of the volume of the sediment to the mass of the sample is the sedimentation volume. (6) pH and conductivity determination: take 5g of sample and prepare a 10wt% filler liquid. Use ST10C-B handheld conductivity meter to measure the conductivity and pH value of the filler liquid.
[0123] Table 1 Test results of different papermaking fillers
[0124] Comparative Example 1 Example 4 Comparative Example 5 Whiteness % 66.4 76.5 90.5 Average particle size μm 13.93 9.55 5.43 <![CDATA[Specific surface area m 2 / g]]> 7.5 7.6 3.1 <![CDATA[Settling volume mL·(10g·24h) -1 > 9.5 9.8 22.5 pH 7.2 6.0 8.8 <![CDATA[Conductivity μS·cm -1 > 282 153 83
[0125] Figure 1 Microscopic morphology pictures of different papermaking fillers, a-Comparative Example 1, b-Example 4, c-Comparative Example 5.
[0126] From Table 1 and Figure 1It can be found that the lithium slag waste of comparative example 1 is in the form of discrete block particles, with a smooth surface and different particle sizes. The whiteness of the lithium slag waste is relatively low, and directly used as a filler, the whiteness of the paper filled with the filler is relatively low, and the color is yellowish. The lithium slag filler of embodiment 4 is after the lithium slag waste is treated with weak acid, and some metals and their oxides in the lithium slag waste can be dissolved and washed and removed, which can effectively improve and promote the whiteness of the paper filled with the filler. Moreover, the particle size of the lithium slag filler is reduced, the content of fine particles is increased, and the smooth surface of the lithium slag filler is destroyed, forming more cross sections, and the surface flatness is reduced, forming more sites combined with fibers, which is conducive to enhancing the bonding strength and retention rate between the filler and the fiber. The particle size of the precipitated calcium carbonate filler of comparative example 5 is smaller than the lithium slag filler of embodiment 4, but the specific surface area of the lithium slag filler is larger than calcium carbonate, which is more conducive to the retention of the filler.
[0127] Test Example 2:
[0128] Characterization of different filled papers
[0129] Determination samples: The filled paper prepared in Examples 4 to 11 and Comparative Examples 1 to 8 were taken as test samples for determination. To ensure the accuracy of the test, the samples were first subjected to 24 hours of equilibrium humidity in a constant temperature and humidity laboratory to reduce the impact of ambient temperature and humidity on the experimental results; each test sample was set up with 5 parallels and the average value was taken. The results are shown in Tables 2, 3 and Figure 2 shown.
[0130] Determination method: (1) Microscopic morphology: stick conductive glue on the sample table, lay the sample flat on the conductive glue and press it firmly. After gold spraying, place the sample table in a scanning electron microscope, observe and record the filler morphology in a vacuum environment with a voltage of 20kV. (2) Whiteness detection: lay the sample flat in the sample press and place it under the intelligent digital whiteness meter for detection. (3) Paper quantity: detect and calculate in accordance with the national standard GB / T451.2-2002. (4) Tensile index: detect and calculate in accordance with the national standard GB / T12914-2008 using a tensile strength tester. (5) Tear index: detect and calculate in accordance with the national standard GB / T455-2002. (6) Filler content: Cut the sample into 5 mm × 5 mm blocks, weigh 2-3 g of the sample, carbonize it, and place it in a muffle furnace. Set the muffle furnace temperature to 550°C ± 25°C and repeatedly burn it until constant weight. The filler content is the ratio of the mass of the residue to the mass of the original sample, expressed as a percentage.
[0131] Figure 2 The microscopic morphology of different filled papers, a-Comparative Example 1, b-Example 4. Figure 2It can be found that in the filled paper of Comparative Example 1, the bulk lithium slag waste particles are mostly attached to the fibers in a discrete state. In the filled paper of Example 4, after the lithium slag waste is treated with acid, the lithium slag filler particles are finer and are mostly filled in the paper in an aggregated state. Moreover, because the lithium slag filler has a smaller particle size after acid treatment, a part of it can be embedded in the gaps between the fibers, and the bonding effect is better, which shows that the acid treatment is conducive to the bonding between the lithium slag filler and the fibers, and is conducive to improving the retention of the filler.
[0132] Table 2 Performance test results of different lithium slag filled paper
[0133]
[0134]
[0135] Table 3 Performance test results of different calcium carbonate filled papers
[0136]
[0137] As shown in Table 2 and Table 3, the mechanical strength of the filled paper is inversely proportional to the filler addition amount and filler content. Comparative Examples and Comparative Examples show that under the same filler addition amount, the strength performance (tensile index and tear index) of the lithium slag filled paper is better than that of the precipitated calcium carbonate filled paper, but the whiteness is lower than that of the precipitated calcium carbonate filled paper. In the lithium slag waste acid treatment, along with the increase of weak acid concentration, the tear index of the lithium slag filled paper and the tensile index of the paper can be improved to a certain extent, but the advantages are still obvious compared with the calcium carbonate filled paper. And the acid treatment can dissolve some metals and oxides thereof in the lithium slag waste, improve the whiteness and compactness of the paper. As can be seen from the filler addition amount and filler content of the embodiments and Comparative Examples, the retention rate of precipitated calcium carbonate is higher than that of the lithium slag filler, but the lithium slag filler is used for the preparation of the filled paper to provide a new filler source for the papermaking industry, and simultaneously provides a filled paper different from the filled paper containing existing fillers, greatly expanding the type and scope of use of the filled paper, and having a broad development prospect.
[0138] Experimental Example 3:
[0139] Determination of the influence of different paper pulps on the properties of filled paper
[0140] Test samples: The filled papers prepared in Example 4, Example 12, and Comparative Examples 9 to 12 were taken as test samples for test. The test method is as shown in Test Example 2. The test results are shown in Table 4.
[0141] Table 4 Test results of the effects of different paper pulps on the properties of filled paper
[0142]
[0143]
[0144] As shown in Table 4, after aminotri (methylene phosphonic acid) and tea polyphenols were added to the paper stock of Example 12, the filler retention rate and compactness of the filled paper were improved, and the tensile index and tear index of the filled paper were significantly improved, and both the tensile index and tear index were improved. By comparing Comparative Examples 9 to Comparative Examples 12, it can be found that the addition amount in a specific ratio in Example 12 has the best improvement effect, indicating that aminotri (methylene phosphonic acid) and tea polyphenols play a synergistic effect, promoting the formation of more complex mechanical entanglements between fillers and fibers, and between fibers inside the paper, thereby improving the internal compactness of the filled paper and the retention rate of lithium slag fillers, and also improving the strength performance of the filled paper; among which, although Comparative Example 12 is not much different from Example 12, considering the addition amount and cost, the addition ratio in Example 12 is more preferably selected.
[0145] It should be noted that in the present invention, the detailed steps of some operations are not described in detail, but belong to the prior art known to those skilled in the art, so they will not be repeated here. In addition, in the present invention, all features such as values, quantities, contents and concentrations defined in the form of numerical ranges or percentage ranges are only for simplicity and convenience. Accordingly, the description of numerical ranges or percentage ranges should be deemed to have covered and specifically disclosed all possible secondary ranges and individual values (including integers and fractions) within the range.
[0146] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit them. In the present invention, not all possible combinations of the various technical features in the various embodiments or embodiments are described. As long as there is no contradiction in the combination of these technical features, the various technical features in the various embodiments or embodiments can be arbitrarily combined, and all possible combinations should be considered to be within the scope of this specification. Although the present invention has been described in detail with reference to the aforementioned embodiments, a person of ordinary skill in the art should understand that the technical solutions described in the aforementioned embodiments can still be modified, or some or all of the technical features can be replaced by equivalents, and these modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A method for preparing lithium slag filled paper, characterized in that: include: 1) Providing a lithium slag filler, wherein the lithium slag filler is prepared by pre-treating lithium slag waste; and providing a lithium slag filler liquid, wherein the lithium slag filler liquid comprises the lithium slag filler and deionized water; 2) Providing a mixed slurry, wherein the mixed slurry is prepared by debonding and refining a plant fiber pulp board; 3) mixing the lithium slag filler liquid with the mixed slurry, and adding a retention and filtration aid to obtain a paper slurry; and 4) After the paper slurry is put on the screen to be formed, it is pressed and dried to obtain lithium slag filled paper; The pretreatment of the lithium slag waste comprises acid treatment, wherein the acid used for the acid treatment is a weak acid, and the weak acid is at least one of phosphoric acid, oxalic acid, and acetic acid; In the paper stock slurry, the amount of lithium slag filler added is 8%-25% of the mass of the mixed slurry.
2. The method for preparing lithium slag filled paper according to claim 1, characterized in that: The pretreatment steps of the lithium slag waste are as follows: using a weak acid solution to stir and soak the lithium slag waste, then washing the lithium slag waste with deionized water until the obtained filtrate is neutral, filtering, and drying the filtrate to obtain a lithium slag filler.
3. The method for preparing lithium slag filled paper according to claim 2, characterized in that: The mass concentration of the weak acid in the weak acid solution is 0.1%-12%; the stirring rate of the stirring and immersing is 700rpm-1000rpm, and the time is 0.5h-2h; the drying temperature is 100℃-115℃, and the time is 4h-7h.
4. The method for preparing lithium slag filled paper according to claim 1, characterized in that: The preparation steps of the lithium slag filler liquid are as follows: mixing the lithium slag filler and deionized water to prepare a suspension, and then subjecting the suspension to magnetic stirring to obtain the lithium slag filler liquid.
5. The method for preparing lithium slag filled paper according to claim 4, characterized in that: In the suspension, the mass concentration of lithium slag filler is 8%-12%; the rotation speed of the magnetic stirring is 900rpm-1200rpm, and the stirring time is 20min-40min.
6. The method for preparing lithium slag filled paper according to claim 1, characterized in that: The plant fiber pulp board is a broadleaf wood pulp board and a coniferous wood pulp board; the mass ratio of the broadleaf wood pulp board to the coniferous wood pulp board is (2.5-3.5):1; the beating degree of the mixed pulp is 35°SR-45°SR.
7. The method for preparing lithium slag filled paper according to claim 1, characterized in that: The retention and drainage aid comprises at least one of cationic starch, cationic polyacrylamide, cationic polyethyleneimine, cationic chitosan and cationic guar gum, and the mass proportion of the retention and drainage aid in the paper stock slurry is 0.01%-2%.
8. The method for preparing lithium slag filled paper according to claim 1, characterized in that: When the web is formed, the web mass concentration is 0.02%-0.03%, the web speed is 150m / min-300m / min, and the pulp-web speed ratio is 0.96-1.01; the pressing pressure is 0.3MPa-0.5MPa, and the time is 3min-5min; the drying temperature is 100℃-115℃, and the time is 7min-12min.
9. A lithium slag filled paper, characterized in that: The lithium slag filled paper is prepared by the preparation method of any one of claims 1 to 8; the basis weight of the lithium slag filled paper is 65g / m 2 -80g / m 2 .